2022
DOI: 10.21203/rs.3.rs-2095871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraint on regional land surface air temperature projections in CMIP6 multi-model ensemble

Abstract: The reliability of the near-land-surface air temperature (LSAT) projections from the state-of-the-art climate-system models that participated in the Coupled Model Intercomparison Project phase six (CMIP6) is debatable, particularly on regional scales. Here we introduce a new method of constructing a constrained multi-model-ensemble (CMME), based on rejecting models that fail to reproduce observed LSAT trends. We use the CMME to constrain future LSAT projections under the Shared Socioeconomic Pathways 5-8.5 (SS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Results in Zhang et al. (2023) indicate the relatively low capability of CMIP6 models in reproducing SAT trend over TP, which may be partly due to the relatively low resolution and uncertainty of the CRU data. Based on finer and more precise station observations in China, the constrained multi‐model ensemble method (CMME) introduced by Zhang et al.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Results in Zhang et al. (2023) indicate the relatively low capability of CMIP6 models in reproducing SAT trend over TP, which may be partly due to the relatively low resolution and uncertainty of the CRU data. Based on finer and more precise station observations in China, the constrained multi‐model ensemble method (CMME) introduced by Zhang et al.…”
Section: Methodsmentioning
confidence: 98%
“…However, in comparison with the Climatic Research Unit gridded data (CRU; Harris et al., 2020), Zhang et al. (2023) found that the CMIP6 MME has a relatively low capability in reproducing the SAT trend in the United States and Asia. Future projections in CMIP6 MME may overestimate the SAT‐rising risk over North America but underestimate the risk over Asia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations